A lingering legacy of leaded gasoline in Southeast Asia - Ray, Iravati (2024)
Recent reports of 1 in 3 children globally having blood lead levels ≥ 5microgram decilitre−1 demands thorough understanding of lead (Pb) sources of the present century and the fate of legacy Pb from the past use of leaded gasoline. The present hotspot of pollution is South and Southeast Asia. To investigate this issue, here we compile Pb isotopic compositions of aerosols (n = 341) along with established and previously excluded sources for Singapore, Thailand, Vietnam, and India. The data was subjected to Bayesian 3D isotope mixing model simulation. Model estimates reveal consistent contributions from natural background. Leaded gasoline is the largest contributor in Southeast Asia (39%). Tertiary coal/fuelwood combustion and ore processing dominate in India, while ship emission contribute up to 15%. Thus, along with Pb from present sources, the historic use of leaded gasoline left a legacy of Pb in soil which is remobilised to the atmosphere after more than two decades of its phase-out.